ADAMTS13 autoantibodies cloned from patients with acquired thrombotic thrombocytopenic purpura: 1. Structural and functional characterization in vitro. Issue 7 (4th April 2016) - Ostertag, Eric M.; Kacir, Stephen; Thiboutot, Michelle; Gulendran, Gayathri; Zheng, X. Long; Cines, Douglas B.; Siegel, Don L.
Abstract : BACKGROUND: Acquired thrombotic thrombocytopenia purpura (TTP) is a life‐threatening illness caused by autoantibodies that decrease the activity of ADAMTS13, the von Willebrand factor–cleaving protease. Despite efficacy of plasma exchange, mortality remains high and relapse is common. Improved therapies may come from understanding the diversity of pathogenic autoantibodies on a molecular or genetic level. Cloning comprehensive repertoires of patient autoantibodies can provide the necessary tools for studying immunobiology of disease and developing animal models. STUDY DESIGN AND METHODS: Anti‐ADAMTS13 antibodies were cloned from four patients with acquired TTP using phage display and characterized with respect to genetic origin, inhibition of ADAMTS13 proteolytic activity, and epitope specificity. Anti‐idiotypic antisera raised to a subset of autoantibodies enabled comparison of their relatedness to each other and to polyclonal immunoglobulin (Ig)G in patient plasma. RESULTS: Fifty‐one unique antibodies were isolated comprising epitope specificities resembling the diversity found in circulating patient IgG. Antibodies directed both to the amino terminal domains and to those requiring the ADAMTS13 cysteine‐rich/spacer region for binding inhibited proteolytic activity, while those solely targeting carboxy‐terminal domains were noninhibitory. Anti‐idiotypic antisera raised to a subset of antibody clones crossreacted with and reduced the inhibitory activity of polyclonal IgG from a set of unrelated patients. CONCLUSIONS: Anti‐ADAMTS13 autoantibodies isolated by repertoire cloning display the diversity of epitope specificities found in patient plasma and provide tools for developing animal models of acquired TTP. Shared idiotypes of inhibitory clones with circulating IgG from multiple patients suggest common features of pathogenic autoantibodies that could be exploited for developing more targeted therapies.